Characterization of Carotenoid Extract and Bioactivity Membrane of the Seeds of Annato (Bixaorellana) - Lia Kusmita (Journal of Global Pharma Technology, 2020)
Bixa Orellana has a typical compound in the form of carotenoids. The types of carotenoids found in these compounds are bixin and norbixin. Both of these compounds have many benefits, one of which is as an antioxidant. Its nature as an antioxidant can also be used as a sunscreen. The purpose of this study was to determine the characteristics of carotenoid pigment in extract of the B.orellana sees membrane. Besides that, it is also to determine its biological activity in the form of antioxidants and sunscreen protectors. The TLC results showed 4 spot of carotenoids in the extract. Spot 1 identified as a bixin compound, because it has the same Rf as the bixin standard. HPLC result showed there were 5 peaks. The peak in tR of 9.046 was identified as norbixin and the peak in tR of 9.819 was identified as bixin. Carotenoid extract on the membrane of the seeds of B. orellana has antioxidant activity 16 times greater than standard bixin. Carotenoid extract at a concentration of 3.10 ppm had an SPF value of 6.27, including the extra protection category, and had a %TE value of 21.71% and Tp of 18.24% in the sunblock category. Keywords: Carotenoid, Antioxidant, Sunscreen, Bixin.